Clinical-pathogenetic and prognostic value of the nitrotyrosine level in the blood serum of patients with coronavirus disease (COVID-19) with pneumonia - O. V. Riabokon; I. O. Kuliesh; I. F. Bielenichev; Yu. Yu. Riabokon (Patologìâ)
The aim of the research is to determine the clinical-pathogenetic and prognostic value of nitrotyrosine levels in the blood serum of patients with COVID-19 with pneumonia in the development of oxygen dependence and the risk of fatal outcome.